2016
DOI: 10.2147/mder.s77657
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the treatment of early-onset spinal deformity: role of the Shilla growth guidance system

Abstract: Early-onset scoliosis is a complex condition with multiple facets. The goal of treating any spinal deformity is to improve the condition of the patient with the least intervention necessary. A system that allows for continuation of natural spinal growth while correcting the deformity should be the goal of treating this complex condition. The SHILLA growth guidance system allows for continued growth of the pediatric spine while correcting and guiding the apex and guiding the future growth of the curvature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Macroscopically visible impurities were also observed in a caprine animal model 17 . Morell and McCarthy and Singh et al also reported tissue inflammation with characteristics of metallosis 16,18 . In the present study, we did not observe periimplantitis, and the metallic particles were much smaller (<25 μm), which may be related to the fact that the tested systems are based on a titanium alloy rather than a steel alloy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Macroscopically visible impurities were also observed in a caprine animal model 17 . Morell and McCarthy and Singh et al also reported tissue inflammation with characteristics of metallosis 16,18 . In the present study, we did not observe periimplantitis, and the metallic particles were much smaller (<25 μm), which may be related to the fact that the tested systems are based on a titanium alloy rather than a steel alloy.…”
Section: Discussionsupporting
confidence: 65%
“…This observation is in agreement with literature reports. Morell and McCarthy 16 observed local metallosis in patients with the steel Shilla system and the metallic debris was up to 45 μm in diameter. Macroscopically visible impurities were also observed in a caprine animal model 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The GRSPSS system represented a similar mechanical construct to the FDA-approved SHILLA device. While there has been good clinical follow-up reported for the SHILLA system at two and five years [21, 26], to date, there is little to no in vitro biomechanical evidence characterizing the stability of either the GRSPSS or the SHILLA systems. This is particularly concerning given that rod breakage has been reported as a frequent complication associated with the SHILLA system, occurring in up to 30% of patients, and may be in association with increased motion at the fused apical segment [2729].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of guided growth systems are Shilla growth guidance system (SGSS) and modern Luque trolley (MLT). SGGS is a new technique based on the use of pedicle screw fixation and dual rods, able to slide in order to follow the spine growth [18,19] . Few studies are available on this technique, showing similar complication rates when compared to TGR [20,21] .…”
Section: Guided Growth and Compression-based Systemsmentioning
confidence: 99%